Use of biologics in the era of COVID- 19: Where do we stand? (2020)
The novel coronavirus disease 2019 (COVID-19) has been spreading for more than 5 months since the World Health Organization declared the COVID-19 pandemic in March 2020. As of August 26, the pandemic had resulted in 23 million confirmed cases and 810,000 deaths worldwide. As the likelihood of prolonged spread without sudden termination of this situation increases, the topic of infection risk in patients treated with biologics is becoming crucial in the dermatologic field. Therefore, we conducted a PubMed search for articles reporting biologics exposure and reviewed guidelines on biologics use published during this pandemic.